SEKOLAH MERDEKA: MODEL PENDIDIKAN BERWAWASAN PANCASILA DAN KEBANGSAAN - Hastangka Hastangka; Sumiyar Mahanani (Universitas Negeri Surabaya, 2021)
ABSTRACTThis study aims to identify and describe the concept of the Merdeka School as a model of education with a national insight and Pancasila. Merdeka School is one of the Community Learning Activity Centers (PKBM) which was established in Yogyakarta in 2020. The existence of this Merdeka School is present in the midst of non-formal and formal education problems that are not in favor of the values of national insight and Pancasila. In addition, the basic idea of the establishment of an independent school saw the current conditions of the school which were not in favor of the needs of students. This type of research is a qualitative research. This study was used to analyze and describe the concepts and policies of the Merdeka School in Yogyakarta. The location of this research was conducted at the Merdeka School in the period from September to December 2020. Sources of research data were obtained through observation and interviews with resource persons. Other data were obtained from documents on independent schools and the results of previous research on school policy. The analysis used in this research uses heuristic analysis. The results of this study indicate that the philosophy and vision and mission of an independent school reflect the direction and orientation of an independent school that builds an atmosphere and principles of national insight and Pancasila principlesKeywords: Independent School, Pancasila, Education, National Insight ABSTRAKPenelitian ini bertujuan untuk mengetahui dan mendeskripsikan konsep Sekolah Merdeka sebagai model pendidikan berwawasan kebangsaan dan Pancasila. Sekolah Merdeka merupakan salah satu Pusat Kegiatan Belajar Masyarakat (PKBM) yang didirikan di Yogyakarta pada tahun 2020. Keberadaan Sekolah Merdeka ini hadir ditengah-tengah persoalan pendidikan non formal dan formal yang kurang berpihak pada nilai nilai wawasan kebangsaan dan Pancasila. Selain itu, gagasan dasar berdirinya sekolah merdeka melihat kondisi sekolah saat ini yang kurang berpihak pada kebutuhan siswa atau peserta didik. Jenis penelitian ini merupakan penelitian kualitatif. Penelitian ini digunakan untuk menganalisis dan mendeskripsikan konsep dan kebijakan Sekolah Merdeka di Yogyakarta. Lokasi penelitian ini dilakukan di Sekolah Merdeka pada periode bulan September sampai dengan Desember 2020. Sumber data penelitian ini diperoleh melalui observasi dan wawancara dengan narasumber. Data lain diperoleh dari dokumen tentang sekolah merdeka dan hasil penelitian sebelumnya tentang kebijakan sekolah. Analisis yang digunakan dalam penelitian menggunakan analisis heuristik. Hasil dari penelitian ini menunjukkan bahwa filosofi dan visi misi sekolah merdeka mencerminkan arah dan orientasi sekolah merdeka yang membangun suasana dan prinsip prinsip wawasan kebangsaan dan Pancasila.Kata Kunci: Sekolah Merdeka, Pancasila, Pendidikan, Wawasan Kebangsaan